Health Management Information Systems for Resource Allocation and Purchasing in Developing Countries - Streveler, Dennis J.; Sherlock, Sheila M. (World Bank, Washington, DC, 2013)
This paper begins with the premise that it is not possible to implement an efficient, modern RAP strategy today without the effective use of information technology. The paper then leads the architect through the functionality of the systems components and environment needed to support RAP, pausing to justify them at each step. The paper can be used as a long-term guide through the systems development process as it is not necessary (and likely not possible) to implement all functions at once. The paper's intended audience is those members of a planning and strategy body, working in conjunction with technical experts, who are charged with designing and implementing a RAP strategy in a developing country.